Impacto del periodismo ambiental y entornos multiculturales que laboran las mujeres en la Hacienda Flumitabaco S.A. Recinto Relampago, cantón Urdaneta, año 2022 - Suarez Tandazo, Jose Armando (2022)
The investigation determines the impact of environmental journalism and the multicultural environment that women work in the Flumitabaco S.A. farm. Relámpago Campus, Urdaneta canton, since it is essential to examine the importance of environmental journalism in the multicultural environments that seasonal women work in the tobacco company, as well as identify the types of multicultural environments and their relationship with preservation and care of the environment, to that through the proposal of a training plan on environmental culture in the quality of life of seasonal women who work in tobacco companies, a fair and equitable environment for them and nature is guaranteed. Therefore, to reach the expected results, the qualitative technique was used for an open result in a fast and efficient way.